Importancia de la innovación y su ejecución en la estrategia empresarial - Haro Carrillo, Fernando Andrés (2017)
One of the main points of this article is to expose some concepts about innovation and clarify them to extract common elements that lead us to develop our own concept. In addition, we analyze the types of innovation that exist because many companies lack the criteria to recognize them or they have maintained such a basic concept of innovation that they only consider itas the creation of a product or service. One of the goals is to disappear that myth. We refer to the innovation not only in function to the area that is going to be improved but to the intensity in which it will be raised. We are clear that innovating is both creating something new, that does not exist, as introducing improvements in existing processes. We also seek to answer the questions: Why do companies innovate? Is it because of a strategy? O Why do they faced with times of crisis and have no choice? One of the answers or reasons comes mainly because at some point in their management they receive or look for information on the reality of the economic and commercial environment of their industry or sector. It is very easy to find within strategic business planning aspects such as objectives, strategies, action plans and budgets. Also, marketing plans linked to internal finance and even internal development plans applied to human resources. But it is not easy to find a plan or strategy of innovation sincemost of organizations do not take it as a strategic axis or as a tool that will solve problems of institutional growth in the short, medium and long term. That is why we mention innovative leadership as a key to transmit or generate a culture of innovation within the company and that it is considered strategic and of equal or greater importance than any unit or department. Achieving this will allow any company that has bet on combining innovation with strategy to think and value what kind of innovation they want and can launch.